The Inhibitory Activities of Mangosteen's Pericarb Extract on Methicillin-Resistant Staphylococcus aureus - sutabhaha, Bongkotwan; Darntrakoon, Unchalee; furuya, Teisuke; Nagumo, Terukazu (Journal of Associated Medical Sciences, 2015)
-